Two-Dimensional Space-Time Image Velocimetry for Surface Flow Field of Mountain Rivers Based on UAV Video - Han, Xiaolin; Chen, Kebing; Zhong, Qiang; Chen, Qigang; Wang, Fujun; Li, Danxun (Frontiers in Earth Science, 2021)
Space-time image velocimetry (STIV) is a promising technique for river surface flow filed measurement with the development of unmanned aerial vehicle (UAV). STIV can give the magnitude of the velocity along the manually set search line thus the application of the STIV needs to specify the flow direction in advance. However, it is impossible to give the velocity direction at any points before measurement in most mountainous rivers due to their complex terrain. A two-dimensional STIV is proposed in this study to determine the magnitude and direction of the velocity automatically. The direction of river flow is independently determined by rotating the search line to find the space-time image which has most prominent oblique stripes. The performance of the two-dimensional STIV is examined in Kuye river and Xiasi river, and the results showed that it is a reliable method for the surface flow field measurement of mountain rivers.